Geometric and metabolic constraints on bone vascular supply in diapsids. (August 2014) - Cubo, Jorge; Baudin, Jéromine; Legendre, Lucas; Quilhac, Alexandra; De Buffrénil, Vivian
<x xml:space="preserve">Abstract</x> Periosteal, endosteal, and intracortical blood vessels bring oxygen and nutrients to, and evacuate the metabolic by‐products from, osteocytes. This vascular network is in communication with bone cells through a network of canaliculi containing osteocyte cytoplasmic processes. The geometric and physiological constraints involved in the relationships between osteocytes (including canaliculi) and blood vessels in bones remain poorly documented from a comparative point of view. Therefore, first of all we tested the first hypothesis (Hypothesis 1) that osteocytes in endotherms may have higher energetic expenditure and may produce more metabolic by‐products than do osteocytes in ectotherms. For this, we tested and found evidence for the prediction, derived from this hypothesis, that the maximum absolute thickness of avascular bone tissue is significantly higher in lepidosaurs than in birds. We also tested two alternative hypotheses explaining the variation of bone vascular density in diapsids. The first of those (Hypothesis 2a) proposed that as body mass increases, the relative effectiveness of vascular supply of the periosteum decreases because its surface increases proportionally to the second power of bone length, whereas bone mass to be supplied increases proportionally to the third power. Accordingly, we predicted and found evidence that bone vascular density is directly related to bone size in both lepidosaurs and birds. The alternative hypothesis (Hypothesis 2b), suggesting that bone vascular density, like mass‐specific resting metabolic rate, may decrease as body mass increases, was refuted by these last results. Knowledge of the cytological relationship between osteocytes and blood vessels in diapsids is poor. Here also we present preliminary results of a comparative cytological study on such a relationship. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 668–677.